A Comparison of Video-Based Interventions to Teach Data Entry to Adults With Intellectual Disabilities: A Replication and Extension. Issue 4 (December 2021) - McDuff, Emeline; Lanovaz, Marc J.; Morin, Diane; Giannakakos, Antonia R.; Kheloufi, Yasmine; Vona, Mélissa
Researchers have demonstrated that video-based interventions are effective at teaching a variety of skills to individuals with intellectual disabilities. To replicate and extend this line of research, we initially planned to compare the effects of video modeling and video prompting on the acquisition of a novel work skill (i.e., data entry) in two adults with moderate intellectual disabilities using an alternating treatment design. When both interventions failed to improve performance, the instructors sequentially introduced a least-to-most instructor-delivered prompting procedure. The results indicated that the introduction of instructor prompts considerably increased correct responding in one participant during video modeling and in both participants during video prompting. Overall, the study suggests that practitioners should consider incorporating instructor-delivered prompts from the onset, or at least when no improvements in performance are observed, when using video-based interventions to teach new work skills to individuals with intellectual disabilities.